On the formation of microstructural gradients in a nickel-base superalloy during electron beam melting. (15th December 2018) - Deng, Dunyong; Peng, Ru Lin; Söderberg, Hans; Moverare, Johan
Abstract: Electron beam melting (EBM) is one of the most widely used additive manufacturing (AM) methods for metallic components and has demonstrated great potential to fabricate high-end components in the aerospace and energy industries. The thermal condition within a melt pool and the complicated thermal cycles during the EBM process are of interest but not yet well-understood, and will significantly affect the microstructural homogeneity of as-manufactured nickel-base superalloy components. To establish the thermal profile evolution during electron beam melting of nickel-base superalloys, Inconel 718 (IN718) is manufactured and characterized in the as-manufactured condition, on account of its representative segregation and precipitation behaviours. The microstructure gradient within a build, specifically the Laves phase volume fraction evolution, is rationalized with the solidification condition and the following in-situ annealing. Precipitations of carbide/nitride/carbonitride, δ and γ′ / γ ′′ are also discussed. Hardness is measured and correlated to the Laves phase volume fraction evolution and the precipitation of γ′ / γ ′′ . The results of this study will (i) shed light on microstructure evolution during the EBM process with regard to thermal history; and (ii) deepen the current understandings of solidification metallurgy for additive manufacturing of Ni-base superalloys. Graphical Abstract: Highlights: Microstructural gradient within one single EBM IN718 build is characterized. Segregation and precipitation behaviours are correlated with thermal profile evolution. The mechanism for forming microstructural gradients in EBM Ni-base superalloys is proposed.